FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MASYARAKAT DALAM MEMILIH JASA LAUNDRY DI SIMPLY FRESH LAUNDRY JALAN BELIMBING NO.1 PEKANBARU - Ega Dwi Fantie; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study is titled "Factors That Affect People's Behavior in Choosing Laundry Services in Simply Fresh Laundry Jalan Belimbing No. 1 Pekanbaru". This study aims to find out the characteristics of the community of laundry service users, the behavior of people choosing to use laundry services and the correlation between the characteristics of laundry service users and the behavior of choosing laundry services in Simply Fresh Laundry Jalan Belimbing No. 1 Pekanbaru. This research uses Quantitative research method. The population in this study was laundry service customers at Simply Fresh Laundry Jalan Belimbing No. 1 Pekanbaru, and a large sample of 98 laundry customers. The variables in this study were internal factor X1 and External factor variable X2, while variable Y was the behavior of choosing laundry. The data was analyzed using product momment correlation. Based on the results of the research analysis showed that the characteristics of the community users of laundry services on average graduated from higher education, the average income of Rp. 3.158.108,- married, the number of family members 3 people. Knowledge price Rp.10.000-Rp.14.000,- with a location distance of 2-3 km and low promotional knowledge. People's behavior choose laundry services based on the frequency of laundry 2x a week, the volume of laundry 5-6 kg in a week and the type of laundry with heavy cloth type. The Behavior Rate of Choosing Laundry category "High" 52.0%, category "Medium" 12.2% and category "Low" by 35.7%. Correlation between characteristics and community behavior in choosing laundry services, namely internal factors (r = 0,546) and external factors (r = -0,229).Keywords: Community Behavior, Laundry Services, Simply Fresh Laundry